2022
DOI: 10.1021/acs.jpclett.2c02847
|View full text |Cite
|
Sign up to set email alerts
|

A General Twisted Intramolecular Charge Transfer Triggering Strategy by Protonation for Zero-Background Fluorescent Turn-On Sensing

Abstract: The exploration of organic fluorescent sensing materials and mechanisms is of great significance, especially for the deep understanding of twisted intramolecular charge transfer (TICT). Here, the electron-donating ability of a chemically protonated amino group and the corresponding excitation primarily ensure the occurrence of excited-state intramolecular proton transfer. Due to the hybridization of the amino group from sp3 to sp2, the steric hindrance effect and conjugative effect together boost the rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…EDA (1), 1,2-propylamine (2), 1,5diaminopentane (3), and 1,12-diaminododecane (4) represent the aliphatic diamines with different chains of carbon atoms, while cyclohexylamine (5), aniline (6), p-toluidine (7), tertbutylamine (8), L-cysteine (9), and hydrazine hydrate (10) are chosen for the different steric hindrance. Meanwhile, it is noteworthy to investigate whether the presence of the O atom in acrylamide (11) and urea (12) would affect the nucleophilicity of the amidogen. Moreover, it is also worthy to verify whether the secondary amines and tertiary amines, such as diethylamine (13), dipropylamine (14), diphenylamine (15), triethylamine (16), N,N-diisopropylethylamine (17), and urotropin (18), would interfere with the distinguishing performance toward EDA.…”
Section: Highly Selective Distinguishing Performance and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…EDA (1), 1,2-propylamine (2), 1,5diaminopentane (3), and 1,12-diaminododecane (4) represent the aliphatic diamines with different chains of carbon atoms, while cyclohexylamine (5), aniline (6), p-toluidine (7), tertbutylamine (8), L-cysteine (9), and hydrazine hydrate (10) are chosen for the different steric hindrance. Meanwhile, it is noteworthy to investigate whether the presence of the O atom in acrylamide (11) and urea (12) would affect the nucleophilicity of the amidogen. Moreover, it is also worthy to verify whether the secondary amines and tertiary amines, such as diethylamine (13), dipropylamine (14), diphenylamine (15), triethylamine (16), N,N-diisopropylethylamine (17), and urotropin (18), would interfere with the distinguishing performance toward EDA.…”
Section: Highly Selective Distinguishing Performance and Mechanismmentioning
confidence: 99%
“…As one of the most representative example of it, ethylenediamine (1,2-diamines, EDA), is one of the primary ingredients used to make the powerful Picatinny liquid explosive . As a typical amine compound, EDA has the typical characteristics of amines (alkalinity and nucleophilicity) as well as corrosivity and toxicity, and due to this reason, WHO has specified 10 ppm as the occupational exposure limit of EDA. , Therefore, it is important to develop highly selective, highly sensitive and rapid response methodologies for on-site EDA detection. Apparently, especially in resource-limited areas, the detection of EDA has been trending away from bulky and time-consuming instruments as well as complex detecting procedures, which needs to be carried out at designated laboratories with trained personnel in most cases. Thus, optical method is considered as one of the most promising approaches for on-site EDA sensing coupled with image analysis techniques because of its visual (with naked-eye) and real-time measurement results, easy operating and portable characteristics. For instance, Lin et al realized a reversible selective fluorescent response for EDA by pillar[5]­arene-based crystalline material (PQ8), although the form of fluorescence quenching made it difficult for naked eye to resolve the concentration of EDA. Huang et al reported nonporous adaptive pillar[4]­arene[1]­quinone crystals for fluorescence turn-on sensing of EDA vapor, while the sensitivity and response time still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular interactions in chemical systems is the heart of chemistry. Chemical probes, including small-molecules, metal–organic frameworks, , fluorescent quantum dots, and nanoclusters, widely used as diagnostic, monitoring, and analytical tools in biochemical, medical, and environmental fields as well as industry, provide useful means for investigating the molecular interactions. Among them, organic small-molecule fluorescent probes have been developed based on receptor–analyte noncovalent interactions or irreversible chemical reactions and possess the advantages of adjustable structures, fast response, high luminous efficiency, and ease of operation, which have drawn considerable attention. Reaction-based fluorescent probes provide higher selectivity with larger spectroscopic changes than fluorescent probes based on noncovalent interactions in most cases, owing to the structural changes from the formation or breaking of the covalent bonds. The excited-state intramolecular proton transfer (ESIPT) science has been widely investigated and shows extremely important significance in the field of displaying, , imaging, lasing, and sensing. , In the field of sensing, as one of the most basic strategies for designing reaction-based fluorescent probes, ESIPT possesses remarkable properties, such as a large Stokes shift, enhanced photostability, ultrafast process, and spectral sensitivity to the surrounding medium, and has been extensively investigated on the design strategies, detailed photophysical properties, and promising applications. In general, the prerequisite for ESIPT is the presence of an intramolecular hydrogen bond between the proton donor (−OH and −NH 2 ) and the proton acceptor (N– and −CO) groups in close proximity to each other in a probe. The general strategy for the development of reaction-based ESIPT fluorescent probes is based on blocking the hydrogen bond donor of the ESIPT fluorophore with a reactive unit that prevents the ESIPT process.…”
mentioning
confidence: 99%
“…The sensing performance of ESIPT fluorescent probes is mainly affected by the spectral properties of the fluorophores, which can be modulated by the hydrogen bonding, , isomerization process, acidity/basicity of the surrounding medium, and chemical modifications on the probes. Among them, the chemical modifications, including π-extensions and substituent groups with electron-donating/electron-withdrawing groups on either or both proton donor moieties, such as the hydroxyphenyl ring, etc., and proton acceptor moieties, such as benzothiazole, benzoxazole, benzimidazole, etc., have attracted considerable attention to investigate the process of ESIPT, which can change the intramolecular hydrogen bond strength and the energy barrier, thus hindering or promoting the occurrence of the ESIPT process. ,,, However, most of these chemical modification strategies focused on the molecular properties and the ESIPT process change from the perspective of theoretical analysis and still lack a systematical investigation regarding how and to which extent the regulation of the probe structure would affect the ESIPT luminescence process and the resulting sensing performance toward the target analyte. Furthermore, it has rarely been applied in practical detection, which should be predominantly due to the challenge of experimentally observing the molecular structure changes in the ESIPT process.…”
mentioning
confidence: 99%
See 1 more Smart Citation